Perancangan Infrastruktur Jalan dan Peningkatan Kompetensi Personil di Desa Tambong Melalui Pelatihan Penyusunan Rencana Anggaran dan Biaya Pekerjaan - Pranowo, Dadang Dwi; Ulfiyati, Yuni; Safitri, Fikca Ayuk; Rifqi, Mirza Ghulam (Politeknik Negeri Pontianak, 2023)
Banyuwangi Regency has development policies and objectives listed in the 2021-2026 Regional Medium Term Development Plan. One of the policies in Medium Term Development Plan is the regional development strategy. Banyuwangi Regency area consists of 25 sub-districts and 189 villages. Most of those villages are scattered in the southern region of Banyuwangi Regency Goverment. With regional boundaries and wide coverage area, Banyuwangi Regency Government has a priority scale in developing villages. In this condition, road facilities cannot be built and developed optimally. Limitation of infrastructure budgeting of the Banyuwangi Regency Regional Government become a problem in Tambong Village. In addition, the limited number of personel who have the ability to prepare planning documents and budget plans is also an obstacle in village infrastructure development activities. Assistance in planning village infrastructure and increasing the capacity of Tambong Village technical personel needs to be carried out so that the development program runs smoothly. Based on this, Banyuwangi State Polytechnic team held training regarding the preparation of a budget plan for technical personnel. Several technical documents needed for funding proposals and infrastructure financing were also prepared in this mentoring activity. This activity is implementing the Tri Dharma of High Vocational Education to the surrounding community. With the implementation of this activity, it is hoped that the transfer of knowledge by the community service team can be realized in the context of increasing the capacity of human resources in Tambong Village.